1999
DOI: 10.1128/iai.67.9.4376-4382.1999
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Surface Protective Antigen (SpaA) of Erysipelothrix rhusiopathiae Serotype 1a Elicits Protection against Challenge with Serotypes 1a and 2b in Pigs

Abstract: Erysipelothrix rhusiopathiae is a causal agent of swine erysipelas, which is of economic importance in the swine industry by virtue of causing acute septicemia, chronic arthritis, and endocarditis. However, little is known about the genetic properties of its protective antigens. Recently, a surface protective antigen (SpaA) gene was identified from serotype 2 in a mouse model. We clonedspaA from virulent strain Fujisawa (serotype 1a) and determined that the N-terminal 342 amino acids without C-terminal repeats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…The Spa types of the Erysipelothrix reference strains with serotypes 1-26 and N were tested using the spa multiplex real-time and conventional PCR assays. Consistent with previous results identified by SDS-PAGE and Western blotting (Makino et al 1998;Imada et al 1999;Shimoji et al 1999;To and Nagai 2007), we found spaA in E. rhusiopathiae serotypes 1a, 1b, 2, 5, 9, 12, 15, 16, 17 and N; spaB (including spaB1 and spaB2) in E. rhusiopathiae serotypes 4, 6, 11, 19 and 21; and spaC in E. sp. strain 2 serotype 18.…”
Section: Strainsupporting
confidence: 92%
See 3 more Smart Citations
“…The Spa types of the Erysipelothrix reference strains with serotypes 1-26 and N were tested using the spa multiplex real-time and conventional PCR assays. Consistent with previous results identified by SDS-PAGE and Western blotting (Makino et al 1998;Imada et al 1999;Shimoji et al 1999;To and Nagai 2007), we found spaA in E. rhusiopathiae serotypes 1a, 1b, 2, 5, 9, 12, 15, 16, 17 and N; spaB (including spaB1 and spaB2) in E. rhusiopathiae serotypes 4, 6, 11, 19 and 21; and spaC in E. sp. strain 2 serotype 18.…”
Section: Strainsupporting
confidence: 92%
“…However, to our knowledge, a quick method such as we describe to determine the spa type of the Erysipelothrix spp. has not been previously reported, in spite of the fact that techniques utilizing SDS-PAGE and Western blotting (Makino et al 1998;Imada et al 1999;Shimoji et al 1999;To and Nagai 2007) and conventional PCR assays for spaA, spaB and spaC (Ingebritson et al 2010) have been recently described. For the spaB gene detection in the multiplex real-time PCR, we first designed a spaB1 probe but found it was not able to recognize serotype 11.…”
Section: Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Virulence factor profiles of isolates from terrestrial animals are fairly uniform (Janßen et al, 2015) and include an immunologically significant surface-protective antigen (Spa) for which three isoforms, SpaA, SpaB and SpaC, have been identified (To & Nagai, 2007). SpaA is a common protective antigen of E. rhusiopathiae (Imada, Goji, Ishikawa, Kishima, & Sekizaki, 1999) and virulence determinant that plays a role in cell adhesion, as well as resistance to serum killing and phagocytosis by macrophages (Borrathybay, Gong, Zhang, & Nazierbieke, 2015).…”
mentioning
confidence: 99%